THE INFLUENCE OF JOB INSECURITY, JOB CHARACTERISTICS, AND WORK CULTURE ON EMPLOYEE PERFORMANCE AT CV. JAYA PERKASA ABADI TANJUNG MORAWA DELI SERDANG,REGENCY - Ayunda Mayyona; Anggia Sari Lubis; Sari Wulandari; Horia Siregar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to determine the influence of job insecurity, job characteristics, and work culture on employee performance at CV. Jaya Perkasa Abadi Tanjung Morawa, Deli Serdang Regency. The research uses a quantitative approach with a population of 300 employees, from which a sample of 75 respondents was selected using the Slovin formula and stratified random sampling technique. Data were collected through questionnaires and observations, and analyzed using multiple linear regression with the help of SPSS version 27. The results show that, partially, job insecurity and job characteristics have a positive and significant effect on employee performance, as indicated by t- values greater than the t-table and significance values less than 0.05. In contrast, work culture does not have a positive or significant effect on employee performance. Simultaneously, job insecurity, job characteristics, and work culture have a significant effect on employee performance, with an adjusted coefficient of determination (R Square) of 0.910, indicating that 91% of the variation in employee performance can be explained by these three variables, while the remaining 9% is explained by other factors outside the scope of this research. These findings highlight the importance of job design and job security in improving employee performance, while also suggesting that organizational efforts to enhance performance should not rely solely on work culture but also consider other motivating and structural factors. The study provides valuable insights for managers and policymakers in optimizing human resource potential to achieve organizational goals.